Synthesis characterization of azo dye 1-{2,4-Dihydroxy-5-[(2-Hydroxyphenyl)Diazenyl] phenyl} Ethan-1-one and spectroscopic characterization of the ligand with iron (III) - Maryam Ashour; Farouk Kandil; Abdulkader Alazrak (Results in Chemistry)
New azo dye 1-{2,4-dihydroxy-5-[(2-hydroxyphenyl) di azenyl] phenyl} ethan-1-one (DHDPE) was synthesized and Characterized by the infrared spectra FTIR, MS spectroscopy,1H NMR. The azo dye has shown analytical properties, the chelate complex has been prepared by reacting the ligand (DHDPE) with the metal ions Fe(III). The formed complex with iron ions has been studied by spectrophotometric method, and complex demeanor after limitation the optimum stipulations and ideal concentration through studying of (UV–Vis) spectrophotometric for complex, The complex had a maximum absorbance at (λmax = 470) in the range of pH values (2−12), and it was found that the complex was stable in a range of pH values (pH =2–3).The structure of the complex has proved to be appropriate to the mole ratio, which was gained from the spectroscopic studies of the complex. The proportion of ligand: metal is (1 L:2 M) for complex ions.